The Clinical Research on Ginger (Zingiber officinale): Insights from ClinicalTrials.gov analysis - Matin, Maima; Matin, Farhan Bin; Ksepka, Natalia; Wysocki, Kamil; Mickael, Michel-Edwar; Wieczorek, Marek; Horbańczuk, Jarosław Olav; Jóźwik, Artur; Atanasov, Atanas G. (Planta Medica, 2024)
Ginger (Zingiber officinale) has a rich history of traditional medicinal use and has attracted a global interest in its health benefits. This study aims to provide insights into the clinical research landscape on ginger, focusing on its pharmacological effects and studied health-related outcomes. The study design involves systematic analysis of data from clinical trials available on ClinicalTrials.gov and discussion of findings in the context of the existing scientific knowledge. A comprehensive analysis of clinical trials registered on ClinicalTrials.gov related to ginger was first conducted, and the scientific background related to specific ginger clinical research avenues was further evaluated through PubMed searches. A variety of trial designs were identified, including treatment, prevention, and supportive care objectives. A total of 188 studies were identified on ClinicalTrials.gov, of which 89 met the inclusion criteria. Among the 89 trials, treatment objectives were predominant (47.2%), and dietary supplements (40.4%) and drugs (27%) were the most prevalent intervention types. These trials covered various health outcomes, such as antiemetic activity, analgesic function, effects on health-related quality of life, blood pressure variation, energy expenditure, and reduction in xerostomia. This study analysis provides a comprehensive overview of the clinical trials landscape on ginger, focusing on its broad spectrum of potential health benefits. While individual trials show promising results, a significant gap in the available data with a low reporting rate of final results is identified, underscoring the need for further research to establish conclusive evidence of gingerʼs therapeutic potentials.
Keywords: Zingiber officinale; ClinicalTrials.gov; antiemetic; clinical trials; pharmacological effects; therapeutic potential; interventional studies; Zingiberaceae